2016
DOI: 10.1007/s10569-016-9712-1
|View full text |Cite|
|
Sign up to set email alerts
|

Determining parameters of Moon’s orbital and rotational motion from LLR observations using GRAIL and IERS-recommended models

Abstract: The aim of this work is to combine the model of orbital and rotational motion of the Moon developed for DE430 with up-to-date astronomical, geodynamical, and geo-and selenophysical models. The parameters of the orbit and physical libration are determined in this work from lunar laser ranging (LLR) observations made at different observatories in 1970-2013. Parameters of other models are taken from solutions that were obtained independently from LLR.A new implementation of the DE430 lunar model, including the li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 26 publications
0
72
3
Order By: Relevance
“…]∕ c is used to describe the oblateness (also called polar flattening) of the core, through its principal components of the MoI tensor  c ,  c , and  c ). While this allowed a close comparison to independent studies (Folkner et al, 2014;Pavlov et al, 2016), the previously reported (Viswanathan et al, 2018) uncertainty on f c does not account for uncertainties from considering a fixed value for c . A different plausible model value of c (e.g., 3 × 10 −4 ) would increase the corresponding value of f c by ≈ 2 × 10 −4 , suggesting an uncertainty Williams et al, 2014).…”
Section: Methodsmentioning
confidence: 78%
“…]∕ c is used to describe the oblateness (also called polar flattening) of the core, through its principal components of the MoI tensor  c ,  c , and  c ). While this allowed a close comparison to independent studies (Folkner et al, 2014;Pavlov et al, 2016), the previously reported (Viswanathan et al, 2018) uncertainty on f c does not account for uncertainties from considering a fixed value for c . A different plausible model value of c (e.g., 3 × 10 −4 ) would increase the corresponding value of f c by ≈ 2 × 10 −4 , suggesting an uncertainty Williams et al, 2014).…”
Section: Methodsmentioning
confidence: 78%
“…The first one is the usual forward-backward test. The full dynamical equations of the Moon from [3] were integrated from 1984 to 2014, and the solution at the last point was taken as the initial condition for integrating backwards, from 2014 to 1984. Differences between the two results are shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…Let us move on to the equation for which the method descibed in this article was developed. This is the equation for the rotational motion of the Moon [2,3], written in a Moon-fixed frame: where ω is the angular velocity, m is the mass of the Moon, N is the external torque, and I(t) is the inertia tensor of the lunar mantle. The inertia tensor is defined as…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations